Pengaruh Latihan Kekuatan Otot Lengan Terhadap Servis Atas Siswa Putri pada Permainan Bola Voli di Ekstrakurikuler SMK Ma'arif 5 Gombong - Dicky Alrizal; Khafid Ikhram (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study aimed to determine the effect of arm muscle strength training on the overhead serve ability of female students participating in volleyball extracurricular activities at SMK Ma'arif 5 Gombong, motivated by the students' poor overhead serve quality resulting from insufficient arm muscle strength and a training method that had remained monotonous and had not specifically addressed biomotor strengthening. This study employed a quantitative experimental approach with a one-group pretest-posttest design, involving 15 female students selected through purposive sampling based on the criteria of active participation in training, freedom from injury, and willingness to complete the entire series of tests. The subjects underwent a progressive arm muscle strength training program for four weeks (12 sessions), beginning with wall push-ups and knee push-ups and advancing to full push-ups combined with dumbbell exercises and medicine ball throws, in accordance with the principle of progressive overload. Overhead serve ability was measured using an adapted test instrument covering five assessment aspects, namely initial stance, arm swing, ball contact, direction and accuracy, and consistency, with a maximum score of 100. The data were analyzed through prerequisite tests (normality and homogeneity), followed by a paired sample t-test at a 5% significance level. The results showed that the mean overhead serve score increased significantly from 55.00 at pretest to 67.47 at posttest, with every subject showing improvement without exception. The greatest gains occurred in the initial stance and direction-and-accuracy aspects, while the ball contact aspect showed the smallest improvement, as it was more strongly influenced by coordination and accumulated technical practice. It can therefore be concluded that a programmed, progressive arm muscle strength training regimen is effective in improving the overhead serve ability of female volleyball extracurricular students, although ideally it should be combined with technical training to achieve more optimal results